(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Distance learning has emerged as a significant educational modality, offering both opportunities and challenges. This article explores the key advantages and disadvantages of distance learning, providing insights into its effectiveness and areas for improvement.